2015
DOI: 10.3233/wor-141839
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of shift-work: The case of Iranian Hospital Security Personnel

Abstract: BACKGROUND: Shift-work, which is an ergonomics issue in workplaces, can negatively affect workers. The security personnel of medical centers in Iran have multiple responsibilities and consequently are exposed to such unwanted situations as observing patients, disputing with patient's attendants, unwanted shift schedules, and being away from family for long periods. OBJECTIVE: This study assessed health problems of Iranian hospital security personnel (shift-worker personnel) using the Survey of Shift-workers (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…(2006) 30) was 3.92, which was higher than those obtained by Abedini et al (2015) 20) , Segawa et al (1987) 32) , and Sugisawa and Uehata (1998) 33) . The relative weight derived by Sugisaw and Uehata (1998) 33) was 34.27%, which was greater than those obtained by Abedini et al (2015) 20) , Pietroiusti et al (2006) 30) , and Segawa et al (1987) 32) . Furthermore, our sensitivity analysis revealed that the removal of any study did not significantly change the pooling OR (95% CI: 1.19-2.30) (Figure 3).…”
Section: Subgroup Analysis: Peptic Ulcerscontrasting
confidence: 49%
See 2 more Smart Citations
“…(2006) 30) was 3.92, which was higher than those obtained by Abedini et al (2015) 20) , Segawa et al (1987) 32) , and Sugisawa and Uehata (1998) 33) . The relative weight derived by Sugisaw and Uehata (1998) 33) was 34.27%, which was greater than those obtained by Abedini et al (2015) 20) , Pietroiusti et al (2006) 30) , and Segawa et al (1987) 32) . Furthermore, our sensitivity analysis revealed that the removal of any study did not significantly change the pooling OR (95% CI: 1.19-2.30) (Figure 3).…”
Section: Subgroup Analysis: Peptic Ulcerscontrasting
confidence: 49%
“…(2014) 26) were 22.92% and 20.30%, respectively, which were greater than those obtained by Abedini et al (2015) 20) , Ahmed and Oraby (2017) 21) , Kim et al (2013) 13) , and Mendes and De Martino (2012) 28) . Furthermore, our sensitivity analysis revealed that the removal of any study did not significantly change the pooling OR (95% CI: 1.28-2.30) (Figure 3).…”
Section: Subgroup Analysis: Indigestionmentioning
confidence: 55%
See 1 more Smart Citation
“…A study among security personnel linked higher BMI with shift work and the effect was thought to be mediated by stress. [ 18 ] The present study did not measure work-related stress but that could be a possible mechanism as well. Occupation-associated physical activity does not seem to explain this because food preparation as well as security involve moderate levels of activity.…”
Section: Discussionmentioning
confidence: 99%
“…The common weakness of these scales is that they only consider the occupational aspect without addressing other effective aspects such as psychosocial ones (David, 2005[ 11 ]). Moreover, it is believed that psychosocial risk factors influence LBP occurrence through interaction with the work environment and individual characteristics (Abedini et al, 2015[ 1 ]; Dehghany et al, 2012[ 13 ]). Therefore, it is highly recommended that the researchers pay more attention to biopsychosocial factors (Mitchell et al, 2009[ 26 ]; George et al, 2012[ 17 ]; Dunn et al, 2013[ 15 ]; Dagenais et al, 2010[ 10 ]) in designing the screening scales (Pincus et al, 2002[ 29 ]).…”
Section: Introductionmentioning
confidence: 99%